ASSESSMENT OF THE QUALITY OF LIFE OF ADOLESCENTS WITH RESPIRATORY TUBERCULOSIS - D. N. Adjablaeva (LLC "Diagnostics and Vaccines", 2017)
Work is dedicated to estimation quality of life of adolescents with different types of tuberculosis. Quality of life of 60 adolescents in age 13-17 years was evaluated with Pediatric Quality of Life Inventory - PedsQL questionnaire. Parents were evaluated separately. Was estimated an initial level of a quality of life before the beginning of hospital treatment. Adolescents have pessimistic and emotional limited subjective estimations of clinical condition and its influences upon all types of vital activity. The indicators quality of life on different scale of the function, exposed parent, were above, than exposed adolescents themselves. The revealed regularities prove to need of performing medical and improving measures, medical-social, clinical-rehabilitation actions and psychosocial correction with considering age features of adolescents, their subjective state and functioning in conditions of a hospital.